The Study of the Three-Dimensional Spin-3/2 Ising Model on a Cellular Automaton (Communications in Computational Physics, 2010)
The spin-3/2 Ising model on the simple cubic lattice with nearest-neighbourferromagnetic bilinear interaction (J > 0) is simulated on a cellular automaton by usingthe cooling algorithm improved from the Creutz cellular automaton. The phasediagrams of the model are constructed in the (D/J, kT/J) and (K/J, kT/J) plane.Comparison of the results are made with those of other methods. The temperaturedependence of the order parameters and associated fluctuations are calculated at variousof the model parameters and the static critical exponents are estimated withinthe framework of the finite-size scaling. The results are compatible with the universalIsing critical behavior except for D/J =−3 and K/J =−2.3.